The stability of bituminous mix design using various types of fillers / Ahmad Fadhley Abdul Majid - Abdul Majid, Ahmad Fadhley (Faculty of Civil Engineering, 2006)
Road construction and maintenance contribute significantly to the growth of Malaysia’s economy. At present, the awareness among the government agencies and contractor in pavement technology in order to improve the pavement systems is responding well. Therefore, the road system exactly is essential for nation’s development and growth. This research focuses on the Ordinary Portland cement (OPC) and quarry dust as fillers in order to determine the optimum percentage in the mix bituminous design. Design mix that contain with 4%, 6%, 8% and 10% of fillers will be tested by using Marshall Test in the laboratory to determine its characteristics and the used in the bituminous mix design. In order to achieve the main objectives, the properties of the other material such as aggregate and bitumen will be firstly measured and determined. After the research, the maximum stability of quarry dust and Ordinary Portland cement is 12.99kN and 13.83kN respectively. The highest stability of mix design occurred at the maximum percentage of filler which is 10%. The optimum percentage of quarry dust is 8% and OPC is 10%.